2019
DOI: 10.3390/cells8101297
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Non-Small Cell Lung Cancer Cells by Oxy210, an Oxysterol-Derivative that Antagonizes TGFβ and Hedgehog Signaling

Abstract: Non-Small Cell Lung Cancer (NSCLC) is a common malignancy and leading cause of death by cancer. Metastasis and drug resistance are serious clinical problems encountered in NSCLC therapy. Aberrant activation of the Transforming Growth Factor beta (TGFβ) and Hedgehog (Hh) signal transduction cascades often associate with poor prognosis and aggressive disease progression in NSCLC, as these signals can drive cell proliferation, angiogenesis, metastasis, immune evasion and emergence of drug resistance. Therefore, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(66 citation statements)
references
References 49 publications
2
64
0
Order By: Relevance
“…(E, F) Inhibitory effects toward TGFβ and Hh signaling. NIH3T3 cells pretreated with or without Oxy210 or Oxy232 for 2 h were stimulated with 20 ng/mL TGFβ (E) or with conditioned medium from CAPAN-1 human pancreatic tumor cells that contain Shh (F) [15, 16] in the presence or absence of the compounds. Cellular mRNAs were extracted to quantify a TGFβ-downstream gene, connective tissue growth factor (CTGF) (E), a Hh target gene, Gli1 (F), and Oaz1 for normalization of CTGF and Gli1 (E, F).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(E, F) Inhibitory effects toward TGFβ and Hh signaling. NIH3T3 cells pretreated with or without Oxy210 or Oxy232 for 2 h were stimulated with 20 ng/mL TGFβ (E) or with conditioned medium from CAPAN-1 human pancreatic tumor cells that contain Shh (F) [15, 16] in the presence or absence of the compounds. Cellular mRNAs were extracted to quantify a TGFβ-downstream gene, connective tissue growth factor (CTGF) (E), a Hh target gene, Gli1 (F), and Oaz1 for normalization of CTGF and Gli1 (E, F).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that Oxy210 inhbited Hedgehog (Hh) and transforming growth factor β (TGFβ) signalings in fibroblastic cells and tumor cells [16]. In contrast, Oxy232, a close structural analogue of Oxy210, is devoid of significant TGFβ inhibitory properties (Figure 2E), but retains inhibitory activity toward Hh signaling (Figure 2F), suggesting that inhibition of TGFβ signaling is not resposible for the anti-SARS-CoV-2 activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations